Studies on Synthesis of Pyrimidine Derivatives and their Pharmacological Evaluation - T. A. Naik; K. H. Chikhalia (E-Journal of Chemistry)
1,3,4-Oxadiazoles were associated with broad spectrum of biological activities including antituberculosis, anticonvulsant, anti-inflammatory, insecticidal, antifungal, analgesic and antitumor properties. Morpholine derivatives find their wide spectrum of antimicrobial activity and exhibit anthelmintic, bactericidal and insecticidal activity. Pyrimidine derivatives are also reported to possess antibacterial, antimicrobial, antifungal, anticancer and anticonvulsant activities. Encouraged by this observations we decided to synthesised novel pyrimidine derivatives.